The Accuracy of Individualized 3D-Printing Template-Assisted I125 Radioactive Seed Implantation for Recurrent/Metastatic Head and Neck Cancer - Bin Qiu; Bin Qiu; Yuliang Jiang; Zhe Ji; Haitao Sun; Jinghong Fan; Weiyan Li; Yuxia Shao; Ping Jiang; Junjie Wang; Junjie Wang (Frontiers in Oncology, 2021)
PurposeTo evaluate the accuracy of individualized 3D-printing template-assisted I125 radioactive seed implantation (3D-PT assisted I125 RSI) for recurrent/metastatic head and neck cancer.Materials and MethodsFrom February 2017 to January 2020, clinical data of 41 patients (mean age, 58.5 ± 16.1 years; 28 males) with recurrent (48.8%)/metastatic (51.2%) head and neck cancer underwent individualized 3D-PT assisted I125 RSI under CT guidance in a single institute were retrospectively reviewed. Total 430 seed needles [mean, 10.5 (range 3–17) per patient] were inserted.ResultsAll seed needles were inserted manually in a single attempt with the technical success rate of 100% without major perioperative complications. The mean needle’s entrance deviation was 0.090 cm (95% Confidence Interval, 0.081–0.098). The mean intraoperative depth and angle of the needle were consistent with that of planned (6.23 ± 0.24 vs. 6.21 ± 0.24 cm, p = 0.903; 83.14 ± 3.64 vs. 83.09 ± 3.66 degrees, p = 0.985, respectively). The mean deviation between the needle’s planned and intraoperative depth and angle was 0.168 ± 0.024 cm and 1.56 ± 0.14 degrees, respectively. The postoperative dosimetry parameters, including D90, D100, V100, V150, V200, conformity index, external index, and homogeneity index, were all well-coordinated with planned dosimetry without significant difference (p = 0.515, 0.662, 0.958, 0.865, 0.872, 0.278, 0.456, and 0.989, respectively).ConclusionsWithin the limitation of this study, individualized 3D-PT assisted I125 RSI may be accurate in obtaining favorable postoperative dosimetry for patients with recurrent/metastatic head and neck cancer.Clinical Trial Registration[website], identifier [registration number].